Towards Sustainable Mineral-Intensive Growth in Orissa : Managing Environmental and Social Impacts - World Bank (Washington, DC, 2012)
The study's objective was to support the socio-economic development program of the Government of Orissa by helping to analyze and formulate practical strategies for strengthening an institutional and regulatory framework with respect to managing the environmental and social impacts of investments in the mining and industry sectors. This study, conducted for about a year, focused on two sets of issues: (i) the need to create mechanisms to share the concentrated benefits of mineral-intensive investments across the community, and (ii) the need to address the externalities of accelerated mineral-intensive through improved enforcement and compliance of environmental and mining regulations. Significant attention was given to the capacity needs of the Orissa Pollution Control Board (OPCB), as the main agency to monitor and enforce compliance with environmental regulations and standards. This analytical work was undertaken with strong support from the Department of Environment (DOE), the Orissa Pollution Control Board (OPCB), Department of Steel and Mines (DoS&M), and the Department of Industry (DoI).